The association of dopamine pathway gene score, nicotine dependence and smoking cessation in a rural male population of Shandong, China. Issue 6 (4th August 2016) - Li, Suyun; Wang, Qiang; Pan, Lulu; Li, Huijie; Yang, Xiaorong; Jiang, Fan; Zhang, Nan; Han, Mingkui; Jia, Chongqi
Abstract : Background and Objectives: Smoking and smoking cessation are both psychological and physiological traits. We aimed to investigate the interaction between dopamine pathway gene scores and nicotine dependence on smoking cessation in a rural Chinese male population. Methods: Participants were recruited from 17 villages in Shandong, China. DNA was extracted from blood sample of 819 participants. 25 single nucleotide polymorphisms (SNPs) in 8 dopamine (DA) pathway genes were genotyped. Weighted gene score of each gene is used to analyze the whole gene effect. Logistic regression was used to calculate odds ratios (OR) and multivariate‐adjusted OR of each gene score for smoking cessation. Multiplicative model interaction was assessed through a cross‐product interaction term of gene score by nicotine dependence in a multivariate logistic regression model. Results: After adjusting for age, occupation, education, marital status, self‐rating anxiety score, and disease status, we observed significant negative associations of catechol‐O‐methyltransferase (COMT), dopamine receptor D2 (DRD2) gene score and smoking cessation, as well as significant positive associations between ankyrin repeat and kinase domain containing 1 (ANKK1), dopamine transporter (SLC6A3), dopamine receptor D4 (DRD4) gene score and smoking cessation. A significant multiplicative model interaction between nicotine dependence and the SLC6A3 gene score on smoking cessation was also observed ( p  = .03). Conclusions and Scientific Significance: There is a significant multiplicative model interaction of SLC6A3 gene score and nicotine dependence on smoking cessation. This finding could help to identify smokers who may be at high risk of relapse, and thus to develop more professional and personalized smoking cessation treatment. (Am J Addict 2016;25:493–498)